Power line communication channel modelling: investigation of Multipath PLC channel model for households - Dipu, Jahidur Rahman; Shohag, Rabiul Islam; Khan, Shahriar; Rizvee, Sayad Hasan (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.